Indias Economy in the New Millennium: Selected Essays - Bimal Jalan; JALAN (Bimal) (New Delhi UBS Publishers Distributors Pvt Ltd, 2002)
Essays on micro, macro economics by a leading Indian economist. includes papers on globalization, exchance issues, and banking. Focus on India, but plenty of comparative analysis. balanced, readable account
Keywords: India; Economic development; Economic history